7. SLEEP QUALITY AND RELATED FACTORS AMONG PRE-OPERATIVE INPATIENTS AT VIETDUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the pre-operation sleep quality and identify related factor among inpatients at Vietduc University HospitalMethods: This is a cross-sectional study, conducted from August 2021 to February 2022 at Neurosurgery Department I, Viet Duc Univesrity Hospital on 247 patients.Results: The sleep quality score of the study subjects was 24.2 ± 5.7. In which, the proportion of patients with mild, moderate, and severe insomnia was 34.8%, 57.9%, and 7.3%, respectively. Patients with chronic diseases will have a shorter sleep time than other subjects (p < 0.05, 95% CI from -1.34 to -0.153). Among the factors related to thequality of sleep in hospital patients include: temperature, odor in the hospital, and health caring activities of health workers.
Keywords: sleep quality; sleep disturbance; pre- operation sleep